Peningkatan Kapasitas Pemerintah dan Masyarakat Nagari Salimpaung Melalui Aplikasi SIANA - Iip Permana; Yulia Hanoselina; Rahmadhona Fitri Helmi; Yuliarti Yuliarti (Jurnal Pengabdian UNDIKMA, 2023)
The purpose of this service is to increase the capacity of the Nagari Salimpaung Government apparatus in utilizing the management of the SIANA application and increase the participation of the Nagari Salimpaung community in obtaining public services. The method used in this service adopts the sprint design method which includes outreach, training and mentoring activities. The instrument for evaluating community service activities uses a questionnaire and is analyzed descriptively. The results of this service show that there is an increase in the capacity of partners, especially the SIANA application operator. This can be seen from the operator’s basic skills in operating the SIANA application.